Characterization and Microwave Absorption Properties of Lead-Free Bi0.5(Na0.80K0.20)0.5TiO3 Synthesized by Sol-Gel Method - Co, Nguyen Dang; Thi Thu Thuy, Bui; Thi Luong, Nguyen; Quoc Viet, Dong; Viet Cuong, Le; Duc Dung, Dang; Duc Quan, Ngo; Mau Danh, Tran; Duc Thang, Pham; Dinh Tu, Bui (VNU Journal of Science: Mathematics - Physics; Vol 38 No 1DO - 10.25073/2588-1124/vnumap.4665, 2022)
Lead-free Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 (BNKT) particles were synthesized by using  sol-gel method. The samples were investigated by X-ray diffractometry (XRD), scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), and vibrating sample magnetometer (VSM). The absorption of microwaves of the lead-free BNKT powders is determined from the magnetic (permeability) and dielectric (permittivity) properties at the frequency range from 2 to 18 GHz. Absorption characteristics of paraffin(wax)-mixed BNKT compounds at different sample thicknesses were also investigated. The microwave absorption properties show that the maximum reflection loss is -21.72 dB (99.9%) at 13.66 GHz with a thickness of 3.2 mm. BNKT composites are thought to be used as a promising microwave absorption material.